(untitled) (Gestão & Regionalidade, 2024)
This article presents as its central theme the loss and waste of food (FLW) and the reuse of agrifood residues resulting from these losses. In this sense, the general objective was to understand the main FLW quantification methodologies and which strategies have been adopted to reduce waste and reuse agro-food residues in light of the Circular Economy (CE) precepts. As a result, four methodologies used internationally were found: Standard to account and report Losses and Food Waste; FAO Methodology; European Union methodology based on the Fusion Project and Food Recovery Hierarchy (FRH). Both adhere to the CE concept based on the reduction of inputs and natural resources, minimization and recovery of agrifood waste through reuse, recycling and composition of by-products that are reinserted in the food supply chain.